Neutropenia Associated with Rifabutin Therapy for Helicobacter pylori Eradication: A Case Report - Gurumurthy, Vaishnavi; Sodhi, Sohail; DiMaggio, Stephen; Garg, Shubham (Archives of Clinical and Medical Case Reports, 2024)
Rifabutin is a less often used medicine, typically used for M.avium complex infection and tuberculosis. However there’s is an increased usage as salvage therapy for drug-resistant H.pylori infection. Rifabutin is the most sought-after antibiotic among individuals with H.pylori that are resistant to clarithromycin or in individuals with previous treatment failures. Nonetheless, it is associated with dangerous complications such as drug-induced neutropenia. It is defined by a significant reduction in neutrophil count. Patients may experience symptoms or be asymptomatic, depending on the severity and underlying medical issues. However, a thorough initial workup by the physician is required to prevent future issues. For patients using rifabutin, a routine follow-up with a complete blood count may be recommended to detect neutropenia early. Prompt treatment with medication withdrawal and consideration of G-CSF such as filgrastim is a given.